The impact of intellectual property rights on international self-employed rates - Andrew E. Burke; Stuart Fraser (Max Planck Institute for Research into Economic Systems, 2005)
The importance of IPR regimes for large firm innovation is well documented but less is known about their impact on typically less innovative self-employed entrepreneurship. The paper sets out to estimate the net effect of the various elements that comprise an IPR regime including the political system, the laws, and institutions as well as a general familiarity with and respect for IPR related products. Cumulatively, the analysis indicates that a well developed IPR regime has a net positive effect on the self-employed sector. Since the self-employed sector is possibly the only segment of the enterprise base where IPRs may be expected to have a negative effect it provides a useful contribution to our empirical understanding of the welfare effects of IPRs on the entrepreneurial economy more widely.
More recent version: http://hdl.handle.net/10419/110995
Keywords: L2; P48; O34; O33; L2; 330; self-employment; intellectual property rights; law; imitation; Immaterialgüterrechte; Unternehmer; Selbstständige; Schätzung; Welt